(3QSGdI aj aVGFd ecI hGdeOjfI hGdHjJ GdMQGe GdebOSi hTF ef JGQjNgGs - (3TgGH GdOjf CMeO GdbdjhHi GdTGaYjs ((3eMeO GdeNGLi GdGRgQi s)
(3ChdgG (B:s
(3CeG HYO agPg fHPg dWjaI eTJedI Ydi eHGMK TQjaI bO MhJ ebGUO GdMLGR heYGdeg eQJHI Ydi ebOeI hHGHjf hNGJeI aGdebOeI ajeG jJYdb HMOhO GdMLGR heMdg hfMh Pdc s
(3BNQgG (B:s
(3hai GdCNHGQ Cf eG Mhdg CQV GdeMTQ hGdefTQ hGddg jQRb ef jTGA HZjQ MSGH hjYWi ef jTGA ceG jTGA dCfg GdcQje GdhgGH hGdMeO ddg QH GdYGdejf hgPG BNQ eG CQOfG EjQGOg Ydi SHjd GdGNJUGQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B148s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs